Testicular tumour presenting as haematemesis. Issue 602 (December 1975) - Lock, M. R.
Abstract : The case is presented of a malignant testicular tumour which presented with a haematemesis due to multiple tumour deposits in both stomach and jejunum. No similar case has been previously recorded. The pathology and aetiology of testicular tumours are discussed.